2022
DOI: 10.1016/j.jpain.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Therapeutic Exercise Modalities on Migraine or Tension-Type Headache: A Systematic Review and Meta-Analysis with a Replicability Analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 82 publications
1
33
0
4
Order By: Relevance
“…In both cases, the evaluation by a physical therapist is recommended. On the other hand, a systematic review conducted in 2022 concluded that craniocervical exercises (involving the deep cervical musculature [ 49 ]) improve disability and quality of life in patients with primary headache, especially in patients with TTH [ 50 ]. In our systematic review we observed morphometric changes in patients with primary headache in comparison with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the evaluation by a physical therapist is recommended. On the other hand, a systematic review conducted in 2022 concluded that craniocervical exercises (involving the deep cervical musculature [ 49 ]) improve disability and quality of life in patients with primary headache, especially in patients with TTH [ 50 ]. In our systematic review we observed morphometric changes in patients with primary headache in comparison with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of dropouts, lost participants can be disregarded or data imputed. Even in the face of this limitation, as the dropout number was below (11.9%) that stipulated in the literature (15%) [ 18 ], it was decided to exclude these patients from the analysis. We recognize that for primary outcomes the sample size calculation was based on previous studies and the expected differences of 3.3 for headache frequency and 1.5 for intensity were not achieved.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current literature, strength exercises have a moderate clinical effect only in patients with tension-type headache. However, with a low quality of evidence [ 18 ]. Although pathophysiology has demonstrated a relationship between migraine and cervical spine in migraine patients [ 9 , 10 ], there is no evidence on the effectiveness of localized exercises, including CMSE.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it was necessary to scale the results to achieve a uniform unit of measure (scale) before combining studies. We interpreted SMD based on previous studies (Varangot-Reille et al, 2022 ) (0–0.2, trivial; 0.2–0.6, small; 0.6–1.2, moderate; 1.2–2.0, large; 2.0–4.0, very large; >4.0, extremely large). The CI showed the degree to which the true value of this parameter has a certain probability to fall around the measurement result, and it gave credibility to the measured value of the measured parameter.…”
Section: Methodsmentioning
confidence: 99%